Design and Simulation of Axial Turbine for Ocean Thermal Energy Conversion (OTEC) - Irfan Syarif Arief; Toni Bambang Musriyadi; Desta Rifky Aldara (Institut Teknologi Sepuluh Nopember, 2018)
Decreasing in fossil energy reserves about 3% every year and has not been matched by the discovery of new energy reserves. Therefore, it is necessary to increase the use of renewable Energy to meet energy needs. Renewable energy is energy derived from sustainable natural processes. Indonesia located in the tropical area, it has a lot of potential ocean energy. OTEC (Ocean Thermal Energy Conversion) is one of many renewable energy sources from the ocean. OTEC or Ocean Thermal Energy Conversion is one of the latest technologies that used the temperature difference between deep and shallow seawater. OTEC system generally used ammonia (NH3) as working fluid. Ammonia is used because it has a relatively low boiling point compared to water. OTEC system consists of evaporators, turbines, generators, condensers, and pumps. In this research, the authors focused on the design of lab-scale OTEC turbines. 2 stage turbine will be varied the tilt which is 0, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50 degree. The computational fluid dynamics (CFD) method is used in this research to simulate the OTEC Turbine. Based on the simulation results, the highest efficiency and net power is a 2 stage 40 degree turbine with 57.45% of efficiency and 287.25 kW of generated power